Purification and characterization of an extracellular beta-n-acetylhexosaminidase from Paecilomyces persicinus. - Eriquez, L A (1979)
Both beta-N-acetylglucosaminidase nad beta-N-acetylgalactosaminidase activities were detected in the culture fluids of Paecilomyces persicinus P-10 after growth in a soybean meal-corn meal medium. The active material was purified by means of protamine sulfate fractionation and ultrafiltration, followed by ion exchange and gel chromatography. The ratio of the two activities remained constant throughout the purification, and the final product was shown to migrate as a single band by using gel isoelectric focusing, disc electrophoresis, and detergent gel electrophoresis. Temperature, pH, inhibition, and kinetic studies were performed to characterize both activities. The molecular weight of the enzyme was estimated to be about 100,000 by high-resolution gel chromatography. Based on the data obtained, it is suggested that both beta-N-acetylglucosaminidase and beta-N-acetylgalactosaminidase activities reside in the same protein.